Treatment-Relevant Findings in Transesophageal Echocardiography After Stroke: A Prospective Multicenter Cohort Study. Issue 1 (9th September 2021) - Thomalla, Götz; Upneja, Mira; Camen, Stephan; Jensen, Märit; Schröder, Julian; Barow, Ewgenia; Boskamp, Stefan; Ostermeier, Birgit; Kissling, Sandra; Leinisch, Elke; Tiburtius, Claudia; Clausen, Henning; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : Background and Purpose: Cardiac ultrasound to identify sources of cardioembolism is part of the diagnostic workup of acute ischemic stroke. Recommendations on whether transesophageal echocardiography (TEE) should be performed in addition to transthoracic echocardiography (TTE) are controversial. We aimed to determine the incremental diagnostic yield of TEE in addition to TTE in patients with acute ischemic stroke with undetermined cause. Methods: In a prospective, observational, pragmatic multicenter cohort study, patients with acute ischemic stroke or transient ischemic attack with undetermined cause before cardiac ultrasound were studied by TTE and TEE. The primary outcome was the rate of treatment-relevant findings in TTE and TEE as defined by a panel of experts based on current evidence. Further outcomes included the rate of changes in the assessment of stroke cause after TEE. Results: Between July 1, 2017, and June 30, 2019, we enrolled 494 patients, of whom 492 (99.6%) received TTE and 454 (91.9%) received TEE. Mean age was 64.7 years, and 204 (41.3%) were women. TEE showed a higher rate of treatment-relevant findings than TTE (86 [18.9%] versus 64 [14.1%], P <0.001). TEE in addition to TTE resulted in 29 (6.4%) additional patients with treatment-relevant findings. Among 191 patients ≤60 years additional treatment-relevant findings by TEE were observed in 27 (14.1%) patients. Classification of stroke cause changed after TEE in 52 of 453 patients (11.5%), resulting in a significant difference in the distribution of stroke cause before and after TEE ( P <0.001). Conclusions: In patients with undetermined cause of stroke, TEE yielded a higher number of treatment-relevant findings than TTE. TEE appears especially useful in younger patients with stroke, with treatment-relevant findings in one out of seven patients ≤60 years. REGISTRATION: URL: https://www.clinicaltrials.gov ; Unique identifier: NCT03411642.